OPINI MAHASISWA ILMU PEMERINTAHAN FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU TERHADAP CITRA DIRI PRESIDEN JOKOWI DALAM VIDEO BLOG KAESANG - Aftania Herlina; Genny Gustina Sari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Utilization of social media today is not only to merely interact, but a place for the public to express public opinion that is human interest. President Joko Widodo is now beginning to use his youtube channel as a media of his presentation, it becomes viral and invites the attention of the public so as to bring up various perceptions. These perceptions and attitudes will shape society opinion and behavior. How society's opinion depends on the role of media and interpersonal communication, as Elizabeth Noelle Neuman puts it in the spiral theory of silence. The purpose of this study is to find out Opinion of governmental students of the Faculty of Social and Political Sciences of the University of Riau on the self-image of President Jokowi in Kaesang's blog video.This research uses quantitative descriptive research type, with survey method approach. Data collection techniques in this study using questionnaires. The total sample for this study of 89 respondents. Sampling using accidental sampling technique. To know opinion on self image, author used a simple linear regression analysis. For the processing of questionnaire, were performed using program Statistic Product And Service Solution (SPSS) Windows version 21.The result of research about opinion of government science student of Faculty of Social and Political Sciences of Riau University to self image of President Jokowi in Kaesang blog video obtained value of regression coefficient in this research is Y = 0,582 + 0,774 X with level significance 0,000 smaller than α = 0, 05. This means that the opinion of the government science students of the Faculty of Social and Political Sciences of Riau University on President Jokowi's self image in Kaesang's blog is 52.8% and is in the medium category. The percentage indicates that a negative self-image has been formed in the perspective of the students. Thus Ho is rejected and Ha accepted.Keywords: Video blog, public opinion, self-image